Association of calciprotein particles measured by a new method with coronary artery plaque in patients with coronary artery disease: A cross-sectional study. Issue 5 (November 2019) - Nakazato, Jun; Hoshide, Satoshi; Wake, Minoru; Miura, Yutaka; Kuro-o, Makoto; Kario, Kazuomi
Highlights: Calciprotein particles (CPPs) measured by a novel method provide useful information in clinical field. Higher CPPs were positively correlated with plaque volume detected by integrated backscatter intravascular ultrasound. High CPP levels might contribute to the risk of plaque vulnerability. Abstract: Background: Calciprotein particles (CPPs) have been suggested to be associated with the degree of coronary atherosclerosis, and have also been established as a molecular marker for clinical outcome in patients with chronic kidney disease (CKD). However, there are several concerns with regard to conventional measurement of CPPs. We therefore developed a new CPP measurement system that can detect both smaller and lower-density CPPs. Methods: We analyzed 71 consecutive patients who underwent percutaneous coronary intervention for acute coronary syndrome (ACS, n  = 29) and/or stable angina pectoris (AP, n  = 42) who did not have CKD of stage 4 or greater. CPP measurement was made using an infrared fluorescent bisphosphonate (OsteoSense, PerkinElmer, Waltham, MA, USA) and a gel filtration method. The coronary artery plaque was analyzed by gray-scale intravascular ultrasound (IVUS) and integrated backscatter (IB)-IVUS. Results: The median CPP level (interquartile range) was 40, 953 (19, 171–74, 131) arbitrary units (AU). When we divided the CPP level into quintiles, the total and lipid plaque volume were incrementally higher with increasing quintile from lowest to highest (both p  < 0.02). After adjustment by age, body mass index, and estimated glomerular filtration rate, which factors were correlated with the above-described plaque components, the top quintile of CPP (>86, 751 AU) had significantly higher total plaque (263 mm 3 vs. 161 mm 3 ; p  = 0.001) and lipid plaque volume (156 mm 3 vs. 89 mm 3 ; p  < 0.001) than the other quintiles. However, these associations were not found for the fibrous or calcified plaque volume. The CPP level was higher in the ACS group than the stable AP group ( p  = 0.02), and the total and lipid plaque volume were also higher in the ACS group than the stable AP group (both p  < 0.05). Conclusions: The results suggested that a high CPP level, as measured by the novel assay, is a surrogate marker for coronary atherosclerosis, especially in lipid-rich plaques, contributing to an increased risk of plaque vulnerability.